Pengaruh Gaya Kepemimpinan dan Kompensasi Terhadap Kinerja Karyawan pada PT Kharismatama Indoalam - Ferris Timothyus Evan; Ika Suhartanti Darmo (UNIVERSITAS KALBIS, 2022)
This research wants to analyze the influence of Leadership Style and Compensation on Employee Performance of PT Kharismatama Indoalam. This study used a quantitative approach with 150 respondents consisting of supervisors and staff in the operational section. Based on the results of this study, it can be concluded that the leadership style at PT Kharismatama Indoalam has a significant impact on the performance of existing employees. Another variable is that Compensation also has a significant influence on Employee Performance. In the last hypothesis it is proven that Leadership Style and Compensation together can have a significant influence on Employee Performance. Based on these results, researchers provide six strategic suggestions that can be used by management in order to improve Employee Performance which will later influence the improvement of the company's quality.